Imidazolate ionic liquids for high-capacity capture and reliable storage of iodine. Issue 1 (December 2018) - Li, Ruipeng; Zhao, Yanfei; Chen, Yu; Liu, Zhimin; Han, Buxing; Li, Zhiyong; Wang, Jianji
Abstract Fast, efficient capture and safe storage of radioactive iodine is of great significance in nuclear energy utilization but still remains a challenge. Here we report imidazolate ionic liquids (Im-ILs) for rapid and efficient capture, and reliable storage of iodine. These Im-ILs can chemically capture iodine to form I-substituted imidazolate ILs with an iodide counterion and the newly formed ILs can absorb iodine to form polyiodide species and low-temperature eutectic salts. For example, choline imidazolate shows iodine capture capacities of 8.7 and 17.5 g of iodine per gram of IL at 30 and 100 o C, respectively, which are, to the best of our knowledge, higher than the values (0.5–4.3 g/g) reported to date. Importantly, iodine can be stably stored in the Im-IL absorbent systems even at 100 o C. The Im-ILs have potential for application in the capture and storage of radioactive iodine. Efficient capture of iodine has important applications in nuclear waste processing. Here a class of imidazolate-derived ionic liquids are shown to chemically capture up to 17.5 grams of iodine per gram of ionic liquid at useful temperatures.